FREQUENCY OF AND FACTORS LEADING TO OBESITY AND OVERWEIGHT IN SCHOOL CHILDREN - Ishaque, Aiesha; Ahmad, Farah; Zehra, Nosheen; Amin, Huma (Journal of Ayub Medical College Abbottabad, 2012)
Background: Obesity is considered as a global epidemic. Obesity in childhood and adolescent is an issue of concern because it is an important predictor of adult obesity. Identifying individuals who are physically inactive, overweight or obese in school going age is very important. The objective of this study was to determine the frequency and factors leading to obesity in school children. Methods: A cross-sectional survey was conducted on children aged 13-16 years. It was a questionnaire based survey with measurement of height and weight. Results: Total 431 children were included in the study. Three hundred and nine (71.7%) of the students were in the normal category, i.e., less than 85th centile while 122 (28.3%) had weight greater than 85th centile and were overweight and obese. Positive association was found between eating out and weight categories, eating breakfast, intake of fresh fruits and vegetables and soft drinks, low physical activity, and increased screen time. Frequency of overweight and obese children was high in children from higher socioeconomic status. Conclusion: There is strong association between strong determinants of obesity and overweight. Health education of students for known risk factors should be integrated with curriculum of science from elementary classes. Keywords: Obesity, Children, Determinants of obesity